COMMUNITY PARTICIPATION IN CUBA: EXPERIENCES FROM A POPULAR COUNCIL - Armando Chaguaceda; Djanamé Daubelcour; Lázaro González (International Journal of Cuban Studies, 2012)
This research analyses community participation in Cuba within a 'Popular Council' on the outskirts of the capital. The work was developed in two stages in 2008 and 2011, following a qualitative research methodology, attending to the discourses and practices of actors.